Biomarcadores de estresse oxidativo em lambaris (Astyanax jacuhiensis) expostos a agrotóxicos - Gonçalves, Carjone Rosa (2018)
Agricultural growth has increased the use of pesticides that are discharged into aquatic eco-systems, thereby disrupting aquatic biota. This study presents two different approaches, the quantification of agrochemicals in Uruguay River water concomitant with the comparative evaluation of biochemical biomarkers in lambaris (Astyanax jacuhiensis), collected in the river, in different stations, at two different points (S1; S4). And, a bioassay for evaluation of biochemical biomarkers in lambaris exposed to carbamate propoxur. The use of biomarkers is used in ecotoxicology as a tool to evaluate the health of organisms exposed to pollutants. Bio-chemical biomarkers offer advantages because they are usually the first responses to envi-ronmental changes that can be detected and quantified. These biomarkers can be damage bi-omarkers, such as lipid and protein oxidation, or defense biomarkers, such as antioxidant en-zymes and non-enzymatic antioxidants. Nine pesticides were identified in river water at all collection sites (S1, S2, S3; S4). The levels of lipid peroxidation (LPO) and carbonyl proteins (PC) in the brain were higher in the summer. In liver and muscle, the highest levels of LPO were found in the spring. PC levels in the liver were higher in the spring and summer in S1. In the brain, Glutathione-S-transferase (GST) increased activity in summer at point S1 and summer and autumn in S4. GST in the gills had the highest activity recorded in the summer, in S1. Catalase (CAT) increased activity during winter and spring, only in S4. In muscle, non-protein thiols (NPSH) had higher levels in the spring, in S1, while NPSH levels in the brain were higher in summer and fall in S1. In the bioassay, the lambaris were exposed to different concentrations of carbamate propoxur (PPX) (5, 15 and 30 μg L-1) for 96h. GST measured in the liver and gills showed reduced activity at all concentrations of PPX tested. The activity of the enzyme acetylcholinesterase (AChE) decreased in the brain and muscle at concentrations of 15 and 30 μg L-1. The content of LPO and hydrogen peroxide (HP) did not differ signifi-cantly. PC content in the brain increased at all concentrations of PPX. In the gills and in the liver, the PC increased in the two major PPX concentrations while in the muscle only at the highest concentration. The variations in the biochemical responses of Astyanax jacuhiensis and the presence of agrochemicals in the water of the Uruguay River, denounce the pollution of Brazilian aquatic ecosystems by pesticides. While numerous of these pesticides are consid-ered to be selective and non-persistent, as PPX, they cause oxidative damage and are capable of modifying the enzymatic activity and anti-oxidant defenses of fish. The results suggest that fish from the Uruguay River Basin are continually exposed to damage from exposure to pesti-cides from the agricultural areas and that carbamate insecticide impairs the ichthyofauna health.